(3GdQhV GdjGfY hBOGH GdeLGeYs - (3SjOj YHO Gddg Hf eSYhO GdOQYj GdJaLQhJjs
(3ChdgG (B:s
(3CeG HYO , CjgG GdCN aEfc WdHJfi Cf CLeY dce eSGFd BOGH GdLeGY heG JYdb Hg hCVja Edjg ef eSGFd GdfcGM heG EJUd Hg djchf CJe CQJHg ai SHI CHhGH(B: (3GdChd ai CMcGe GdfcGM hGdJQZjH ajg , GdKGfi (B: (3ajeG jLH Ydi GdRhL hGdKGdK (B: (3aj s
(3BNQgG (B:s
(3JfbU ef BNQgG , hBNQ GdehLhO ajgG (B: (3hajgG dYQb GdfSGA eG LGA Yfg Udi Gddg Ydjg Cfg TcG Zdjg QLd YQb GdfSG ` hCfg GQGO bWYg , abGd (B: (3dG JbWYI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HYV YHGQGJgG HGdMeQIs
(3fSNI egJQFI s
(3MhGagG eJBcdI LOkG s
(3eWGdYI s
Keywords: (3Gdabg GdESdGejs